Intraorbital ancient pilocytic astrocytoma of the optic nerve in neurofibromatosis type 1 patient presenting with sudden ocular pain. (24th February 2018) - Motoyama, Haesu Lee; Yamada, Sohsuke; Nakada, Satoko; Kurose, Nozomu; Tanimoto, Akihide
Optic nerve pilocytic astrocytoma is an uncommon but well-known entity; however, intraorbital ancient pilocytic astrocytoma of the optic nerve is extremely rarely reported. To our knowledge, this is the first detailed description regarding the intraorbital ancient pilocytic astrocytoma, reported in available English literature, to date. We presented an extremely unusual neurofibromatosis type 1 case of a 17-year-old male's sudden ocular pain secondary to intraorbital pilocytic astrocytoma of the optic nerve with markedly cystic degeneration, fluid production, and hemorrhage, due to ancient and possibly ruptured glioma. Future prospective studies are required to validate the significance of intraorbital ancient pilocytic astrocytoma arising from the optic nerve and the close correlation with ruptured cystic degeneration and ocular pain, after collecting and investigating a larger number of its cases examined.